A Cost-Benefit Analysis of Advocacy and Legal Advice Centers - Hoechst, Jonathan; McBride, Jonathan; Nischan, Ulrike; McAtee, Rebecca (My University, 2010)
Corruption is a significant concern, especially for developing nations. Evidence indicates that high levels of corruption can have negative political, social, and economic repercussions -- all contributing to low levels of growth in gross domestic product. Through the method of cost-benefit analysis, this report evaluates the effect of Transparency International's Advocacy and Legal Advice Centers as an anticorruption strategy. The analysis suggests that the centers are an extremely cost-effective method of reducing corruption.